The influence of new 1,2,3-triazolo-1,4-benzodiazepine derivatives on the muscle tone of rodents - I. V. Botsula; I. V. Kireyev; O. M. Koshovyi; V. A. Chebanov (Zaporozhye State Medical University, 2023)
Anxiety disorders represent one of the most prevalent categories of psychiatric illnesses, affecting individuals regardless of gender, age, or social standing. They result in substantial personal and societal costs. The pursuit of novel pharmacological approaches for treating these disorders is driven by the increasing medical necessity to enhance the effectiveness and safety profiles of anxiolytic medications. Due to the fact that benzodiazepines and their derivatives have anti-anxiety, hypnotic-sedative, antidepressant, anticonvulsant, and muscle relaxant properties, they occupy a leading place in the treatment of anxiety disorders. An essential aspect of investigating the pharmacological activity of new triazolobenziazepine derivatives is assessing their impact on rodent muscle tone and coordination of movements. The aim of the work is to find out the influence of new 1,2,3-triazolo-1,4-benzodiazepine derivatives on the muscle tone of rodents in the "vertical grid" test and coordination of movements using the rotarod test. Materials and methods. The objects of the study were 5 new derivatives of 1,2,3-triazolo-1,4-benzodiazepines. Before conducting in vivo experiments, these derivatives were mixed with lactose at a ratio of 1:1000. The "vertical grid" test and rotarod test (rotating rod test) were used to reproduce the model of motor behavior of rodents. Results. The presence of a tendency to the manifestation of a myorelaxant effect in the "vertical grid" test was established. The indicator of the total duration of detention at the facilities was similar and did not differ significantly in the control and experimental groups at doses of 0.50 mg/kg and 0.75 mg/kg. Derivatives MA-252, MA-253 and MA-254 at a dose of 1 mg/kg reduced the total duration of retention on the vertical grid, which indicates their mild muscle relaxant effect. In the rotating rod test, MA-253 derivative at a dose of 1 mg/kg increased the retention time on the rotarod, which demonstrates greater physical endurance of the animals of these experimental groups. Conclusions. The study's findings indicated that the 1,2,3-triazolo-1,4-benzodiazepine derivatives did not exhibit an adverse impact on movement coordination. Some of these derivatives demonstrated a mild muscle relaxant effect. These results support the need for further research into their influence on spontaneous motor activity. Additionally, there's a necessity to determine the dosage regimen, establish an effective dose, and adapt it for human use.